The Self as Image and Suddenness: Some Remarks on Plotinus’ Noetic Life - Lavecchia, Salvatore (Peitho. Examina Antiqua, 2019)
This article focuses on certain dimensions of Plotinus’ notion of the noetic self, which so far have not received sufficient scholarly attention. The evidence of Enn. V 8 makes clear the assumption about the inexhaustible generativity of the noetic self. This generativity implies an intimate relation with the notions of image and suddenness: the former is intended as a medium of unconditional self-transparency, whereas the latter is understood as pointing to the unlimited newness that is characteristic of the noetic life, which, according to Plotinus, consists in an indissoluble unity of identity and alterity (Enn. VI 7.13). The aforesaid notions make it reasonable to view Plotinus’ concept of noetic self as pointing to a predominantly relational and dynamic ontology, in which essentialism presupposes no staticity whatsoever, but can rather be seen as a perspective that leads to the development of a harmonious and non-narcissistic creativity.